Odpowiedzi

2010-02-17T16:32:52+01:00
W wyrażeniu 4x² -20x , wyłącz przed nawias
a)4x² -20x=x(4x-20)

b)4x² -20x=4(x2-5x)

c) 4x² -20x=4x(x-5)

d) 4x² -20x=20(1/5x2-x)

e) 4x² -20x=20x(1/5x-1)

f) 4x² -20x=-x(-4x+2x)

g) 4x² -20x=-4(-x2+5x)

h) 4x² -20x=-4x(-1x+5)

i) 4x² -20x=-20(-1/5x2+x)

j) 4x² -20x=-20x(-1/5x+1)

13 3 13
Najlepsza Odpowiedź!
2010-02-17T16:38:23+01:00
A. x (4x-20)
b. 4 (x2 - 5x)
c. 4x (x-5)
d. 20 (1/5x2-x)
e. 20x (1/5x-1)
f. -x (-4x +20)
g. -4 (-x2 +5x)
h. -4x (-x +5)
i. -20(-1/5x2+x)
j. -20x(-1/5x+1)




12 4 12